Guideline for screening antioxidant against lipid‐peroxidation by spectrophotometer. Issue 2 (28th March 2023) - Li, Yue; Si, Dun; Sabier, Maidinai; Liu, Jingjing; Si, Jinping; Zhang, Xinfeng
Abstract: Lipid peroxidation (LPO), an oxidative chain reaction often occurring in the human body and food, is harmful to human health. Due to its convenience and low cost, this guideline highlights the benefits and drawbacks of LPO models by spectrophotometer in vitro and in vivo. The preparation process and reaction mechanism of lipid substrates, oxidation triggers and detection methods are discussed in this paper to better screen antioxidants. The lipid substrates mostly consist of rat liver/brain homogenate, microsomal, low‐density lipoprotein (LDL), and linoleic acid (LA), are appropriate for modeling oxidative damage in a variety of situations. Transition metals, ascorbic acid, 2, 2′‐azobis (2‐amidinopropane) hydrochloride (AAPH), sodium Nitroprusside (SNP), 3‐morpholinosydnonimine (SIN‐1) and nicotinamide adenine dinucleotide phosphate (NADPH) make up the majority of the oxidizing triggers. The following LPO quantification techniques have been reviewed: (a) thiobarbituric acid reactive substances (TBARS) assay, (b) measurement of conjugated‐diene (CV), (c) β ‐carrot bleaching assay, (d) thiocyanate method, (e) ferrous oxidation‐xylenol orange (FOX‐2) assay. It can be concluded that more than one test system should be applied to obtain comprehensive results. In a word, this guideline provides a scientific basis for future research on antioxidants screening in food and body systems. Abstract : In this article, several methods with biological system similarity for screening antioxidants in vitro and in vivo were reviewed, including preparation of lipid substrates, induction of oxidation triggers and quantification of antioxidant capacity. The conclusion is that multiple testing systems should be applied to obtain comprehensive results.